2018
DOI: 10.3390/socsci7120268
|View full text |Cite
|
Sign up to set email alerts
|

Noise Complaints between Japanese Neighbors and Migrants in Rural Japan: From the Perspectives of Noisemakers

Abstract: This paper focuses on the narratives and embodiment of noisemakers in noise complaints in a small town of rural Japan. By building on the intersection of sound studies, body, and migration, this paper aims to critically address the long-discussed concept of ‘noise’ through the perspectives of migrants who are perceived as ‘noisemakers’ in the neighbor relations between Japanese neighbors and migrants. This study was conducted through months of fieldwork in a small town in Japan, in which an ethnic concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Furthermore, Legewie and Schaeffer (2016) found that there is a positive relationship between ethnic and racial diversity in a neighborhood and the number of noise complaints. Both Mutiara (2018) and Stokoe and Wallwork (2003) agree that those who make noise complaints against others have an "us versus them" mentality. Finally, Mutiara (2018) finds that noise complaints come with an unequal distribution of social power within the neighborhood.…”
Section: Noise Complaintsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Legewie and Schaeffer (2016) found that there is a positive relationship between ethnic and racial diversity in a neighborhood and the number of noise complaints. Both Mutiara (2018) and Stokoe and Wallwork (2003) agree that those who make noise complaints against others have an "us versus them" mentality. Finally, Mutiara (2018) finds that noise complaints come with an unequal distribution of social power within the neighborhood.…”
Section: Noise Complaintsmentioning
confidence: 99%
“…Both Mutiara (2018) and Stokoe and Wallwork (2003) agree that those who make noise complaints against others have an "us versus them" mentality. Finally, Mutiara (2018) finds that noise complaints come with an unequal distribution of social power within the neighborhood. Therefore, where neighbors have less cohesion, we should expect more noise complaints.…”
Section: Noise Complaintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indonesian migrant workers alone in Japan recorded 49,982 people living in Japan both legally and illegally. Since 1998, the chairman of the factory association in Oarai has invited Japanese descendants and migrants from North Sulawesi to work in the seafood industry, so it is not new that many Indonesian migrant workers in Japan today 11 .According to statistics from the Indonesian Migrant Workers Protection Agency, Japan received 486 Indonesian migrant workers in 2019. The figure decreased from 538 in 2017, which makes Japan number 13 for the largest Indonesian migrant worker placement country.…”
Section: Figure 1 Ratio Of Foreign Workers By Nationalitymentioning
confidence: 99%